Serum cystatin C unmasks renal dysfunction in cirrhosis and performs better in estimation of glomerular filtration rate - Velayudham, Balaraman; Thomas, Remi George; Vasudevan, C.; Senthilkumar, R. P.; Thirumalvalavan, Murugesan (Saudi journal of kidney diseases and transplantation, 2020)
In this study, we aimed to measure glomerular filtration rate (mGFR) using 99Tc DTPA in patients with Child-Pugh C cirrhosis and normal serum creatinine levels; and to compare the performance of creatinine and cystatin C-based equations [estimated GFRs (eGFRs)] to 99TcDTPA GFR in the same group. We selected a group of 65 consecutive patients with advanced liver cirrhosis and apparently normal renal function by serum creatinine alone. Patients with confounding and reversible factors were excluded. Demographic data, blood, urine, and imaging tests along with simultaneous measurement of serum creatinine and cystatin C were analyzed. The GFR was measured by 99Tc DTPAscintigraphy (mGFR) in 41 patients. We compared the performance of chronic kidney disease epidemiology collaboration (CKD-EPI-creatinine, CKD-EPI-cystatinC, CKD-EPI-creatinine-cystatinC) and Modification of Diet in Renal Disease equation equations for bias (mean difference), precision (root mean square error), and accuracy (P10 and P30). Bland–Altman plots were used to show the agreement of eGFR and mGFR. Twenty-five out of 41 patients (61%) had significant renal dysfunction (GFR ≤60 mL/min/ 1.73m2) by 99TcDTPA in our study and three patients were already in Stage 4 CKD. Unlike serum creatinine, serum cystatin C values were deranged in these patients. Among all GFR estimating formulae, CKD-EPI-creatinine-cystatinC combined equation had the least bias (−2.3), superior precision (7.1), highest P30 accuracy (78%), good sensitivity (87.5%), and best specificity (96%) in our study. Two-thirds of patients with cirrhosis had significant renal impairment despite having normal serum creatinine. Isolated serum creatinine values are misleading in cirrhosis. Cystatin C unmasks renal dysfunction in these patients. CKD-EPI-creatinine-cystatinC equation showed the best correlation and accuracy with 99TcDTPA GFR in our study. Creatinine based GFR estimation is fallacious in cirrhosis. Cystatin C and equations based on it may be worthwhile in liver disease.